APLIKASI KARTU RENCANA STUDI (KRS) PADA STMIK NURDIN HAMZAH JAMBI: APPLICATIONS, CONTRACTS LECTURES, VISUAL BASIC 2013, THE LIBRARY - Purnama, Fery; Saputra, Anwar (FORTECH (Journal of Information Technology), 2017)
Application which is a computer program that made to do and implement a special assignment from users, in which the application can be used many people to ease in the daily. in STMIK Nurdin Hamzah contract lecture is still classified as manual, especially student who have to write the registration form study as many as three sheets of in accordance with the subjects that will taken, that calls for more of the time and energy. This is exactly the foundation for a review what do research on STMIK Nurdin Hamzah. In conducting the study, the authors using some of the research methodology, including field research, to the library and laboratory. This application was built with support for Visual Basic 2013, Crystal Report 13 as well as additional libraries are required. Furthermore, the application that has been built is expected to be more helpful STMIK Nurdin Hamzah in contracting lectures, such as the students taking the course. From the results of this study concluded contract applications lectures pas STMIK Nurdin Hamzah were made with the aim of helping STMIK Nurdin Hamzah in data processing of the contract relating to the students, and the application is built with support for Visual Basic 2013, Crystal Report 13 as well as additional libraries are required.